Karakteristik Sendi Siku Anjing Kintamani dengan Teknik Pencitraan Radiografi - Murtiningrum, Fitria Senja; Widodo, Setyo; Soehartono, Raden Harry; Rahmiati, Dwi Utari; Noviana, Deni (Jurnal Veteriner, 2023)
The Kintamani dog was designated as the first Indonesian native dog by the Indonesian Kinology Association (Perhimpunan Kinologi Indonesia/Perkin) in 2006 and has been officially registered as an Indonesian native world dog by the Fédération Cynologique Internationale (FCI) on February 20 2019, under the breed name Anjing Kintamani – Bali. This study aims to evaluate the radiogram of the elbow joint in Kintamani dogs based on FCI assessment standards. The research samples used were radiograms of 34 Kintamani dogs aged 12 to 24 months, consisting of 19 male dogs and 15 female dogs. Forelimb radiographs were taken in two positions, mediolateral flexion 15° and craniocaudal pronation 15°. Radiograms were taken using computerized radiography (CR) and digital radiography (DR), then interpreted and analysed using Digimizer software. The interpretation of the elbow joint is done descriptively based on the presence of primary lesions and/ or osteoarthrosis in the elbow joint. A qualitative analysis was carried out regarding the normal anatomical structure of the elbow joint of the Kintamani dog according to the standards set by the FCI. Based on the FCI assessment score for the forelegs, 33 Kintamani dogs were assessed as normal (FCI grade 0). Only one Kintamani dog was assessed as having mild elbow dysplasia (FCI grade 1), as indicated by the presence of >2 mm osteophytes. Complete knowledge of the anatomy and radiography position is very necessary in determining the prognosis of elbow dysplasia in order to support efforts to breed the Kintamani dog as the first Indonesian native world dog.